The analysis of NMR J-couplings of saturated and unsaturated compounds by the localized second order polarization propagator approach method - Zarycz, Maria Natalia Cristina (2012)
Calculations of NMR J-coupling with polarization propagators are not invariant under unitary transformations at second order level of approach, second order polarization propagator approach (SOPPA). They are only invariant at first order or random phase level of approach (RPA). We performed “localized” SOPPA (Loc-SOPPA), calculations of J-couplings applying two different schemes for the localization of molecular orbitals(LMO): Foster-Boys and Pipek-Mezey. We show here that results of such Loc-SOPPA calculations are different though not much: they are less than 6% different in the worst case. Therefore it is possible to apply them with confidence in the analysis of the transmission of different coupling mechanisms within the molecule. We are able now to get reliable information on what LMOs are the most important (and so which are not important) for a given J-coupling in a molecule. This information can then be used for selecting which are the paths that should be described with the highest possible accuracy for that J-coupling calculation. A few unsaturated compounds are analyzed: ethene, trans-difluoroethene or DiF-ethene, and imine. It is shown that different lone pairs (of pz or px/y type) are responsible for the vicinal F-F J-coupling in DiF-ethene; and also the fact that the main LP contributor is not the same for the fermi contact and the spin-dipolar mechanisms.We also studied phosphorous containing compounds such as phosphine and cis-propylene phosphine. In both cases the analysis of the main LMO contributing to one-bond P-H coupling and through-space P-C coupling were performed. The above mentioned unsaturated molecular systems have quasiinstability problems that arise at RPA level of approach. We show here that they are mostly originated in the antibonding π* LMO, corresponding to the C=C or C=N double bonds. We performed the analysis of the origin of quasiinstabilities for the SD mechanism. The contribution of each kind of excitation terms to SOPPA calculations were considered, meaning the main contributions by single and double excitations. It is shown that one can get more than 97% of the total electron correlation contribution when including terms that mainly contain single excitations (though double-excitation matrix elements should still be calculated).